Entrepreneurial Learning Acquired Through Internships in the Hospitality Industry - LU, H-T; Wang, Y-C (KnE Social Sciences, 2018)
The purpose of this study is to examine how internships develop and enhance the entrepreneurial spirit of university students. A questionnaire was designed and issued twice, that is, before and after the students’ internships. An independent-sample t-test analysis was used to compare mean scores before and after the internship. The results show that internships provide students with more confidence to identify opportunities and solve problems, enhance interpersonal and communication skills, and render interns more action-oriented. The study also reveals that students lack certain key abilities. Overall, the study provides information for both students and university teachers concerning the importance of internships. Keywords: entrepreneurial learning, hospitality industry, multi-skills